Anticlastogenic and hepatoprotective effects of Kolaviron on sodium valproate-induced oxidative toxicity in Wistar rats. Issue 1 (1st January 2021) - Ola, Olaniyi Solomon; Adewole, Kayode Ezekiel
ABSTRACT: Kolaviron (KV) is a biflavonoid isolate mixture of defatted Garcinia kola seed extract patented for treatment of hepatic disorders and inflammation-related conditions. The clinical and experimental-based reports on liver impairment of valproic acid, a front-line synthetic drug used in the treatment of epilepsy gained public attention. Therefore, the mitigative effect of Kolaviron on perturbed redox status and genotoxicity caused by sodium valproate was investigated in murine hepatic tissue. Kolaviron at a dose of 200 mg/kg and sodium valproate (SVP) at a dose of 500 mg/kg were administered orally and consecutively, at an hour interval once a day for two weeks. Treatment with Kolaviron reduced the SVP-increased activities of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase. Significant increase ( P < 0.05) in plasma advanced oxidized protein products (AOPPs) and concomitant reduction in total thiol were observed in liver of SVP-treated rats. Supplementation with Kolaviron significantly reduced the SVP-induced AOPP formation and restored the plasma surfydryl protein level. In addition, Kolaviron ameliorated the SVP-mediated decrease in the activities of glutathione-S-transferase, superoxide dismutase, catalase and reduced glutathione level ( P < 0.05). Co-treatment of rats with Kolaviron elicited antigenotoxic effect by inhibiting the induction of micronucleated polychromatic erythrocytesin bone marrow and prevented the formation of DNA fragmentation promoted by SVP. In conclusion, Kolaviron offered protection against sodium valproate-induced genotoxicity, augmented antioxidant status and prevented hepatic oxidative stress in rats.